2008
DOI: 10.1080/15470650802231861
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Marijuana Effect Expectancy Questionnaire-Brief

Abstract: The purpose of this study was to evaluate a brief version of the Marijuana Effect Expectancy Questionnaire (MEEQ; Schafer & Brown, 1991). The original MEEQ was reduced to 6 items (MEEQ-B). Principal component analysis (PCA) was performed and two factors were identified (positive effects and negative effects) accounting for 52.3% of the variance. Internal consistencies (0.42 to 0.60) were slightly lower than those of the original MEEQ. The negative effect expectancy scale correlated with criterion variables tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 22 publications
4
34
1
Order By: Relevance
“…Another potential limitation of the current study is that some of the expectancies scales used had low internal consistency (i.e., both subscales of the MEEQ-B and the social effects subscale of the CEQ). Of note, the estimates for MEEQ-B in the current study were similar to those reported in previous studies examining measures of marijuana and alcohol expectancies (23,31); having only three positive and three negative items in the MEEQ-B may account for the low internal consistency. The low reliability of the CEQ subscale may also reflect the fact that measure was adapted from an alcohol measure.…”
Section: Discussionsupporting
confidence: 87%
“…Another potential limitation of the current study is that some of the expectancies scales used had low internal consistency (i.e., both subscales of the MEEQ-B and the social effects subscale of the CEQ). Of note, the estimates for MEEQ-B in the current study were similar to those reported in previous studies examining measures of marijuana and alcohol expectancies (23,31); having only three positive and three negative items in the MEEQ-B may account for the low internal consistency. The low reliability of the CEQ subscale may also reflect the fact that measure was adapted from an alcohol measure.…”
Section: Discussionsupporting
confidence: 87%
“…Scales have been developed to assess marijuana expectancies (Buckner et al, 2013;Torrealday et al, 2008), motives for using (Lee et al, 2009;Simons et al, 1998), and consequences (Copeland et al, 2005;Simons et al, 2012) in the young adult population, and recent work has looked at self-efficacy to employ use-reduction strategies (e.g., confidence to use cognitive behavioral strategies to cut down) among a community sample of marijuana users (Davis et al, 2014a(Davis et al, , 2014b. However, there is a need for a broader behavioral measure of protective strategies beyond use reduction among young people.…”
Section: Y Oung Adults Are An At-risk Populationmentioning
confidence: 99%
“…Expectancy theory originally sought to explain why individuals drink alcohol (Goldman, Del Boca, Darkes, 1999; Goldman, 1994) and has been applied to adolescent marijuana use as well (Aarons, Brown, Stice, & Coe, 2001; Torrealday et al, 2008). The theory suggests that individuals learn, through observation and experimentation, positive and negative beliefs about how a drug will affect them.…”
Section: Expectancy Theorymentioning
confidence: 99%